Identification of bioactive phytochemicals using GC-Mass and TLC to the estimation of antimicrobial susceptibility of plant extracts - Ali, Muna Jalal; Makky, Essam A.; Zareen, Seema; M. M., Yusoff (IOP Publishing, 2019)
This study aims to evaluate the constituent compounds of plant extracts and their antimicrobial activity. Four different ethnomedicinal plant extracts including Piper nigrum, Nigella sativa, Cinnamomum zeylanicum, and Elettaria cardamomum were tested for antimicrobial susceptibility profile identified using GC-Mass and demonstrated TLC analysis. We found the combined action of ethanol plant extracts (alone) against oral isolates showed a synergistic effect profile up to 32.20% when combination A (Ci/Ca) was added. The stearic and palmitic acids were the major constituent compounds of plant extracts which was exhibited high antimicrobial susceptibility against the bacterial isolates. We conclude that the stearic and palmitic acids were major constituent compounds of plant extracts.